2017
DOI: 10.5897/ajar2017.12530
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus fixation and its relationship with physicochemical properties of soils on the Eastern flank of Mount Cameroon

Abstract: The Eastern flank of Mount Cameroon is made up of human settlement and agricultural activities. Determination of phosphorus (P) fixation characteristics of soils around this region is important for a clean environment and economic fertilizer application. The objectives of this study were to evaluate Pfixation characteristics of soils within the region and identify factors contributing to P-fixation. Composite surface soil samples from five sites (between 36 to 1006 m) were collected and analyzed for physicoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…At these pH values, Al, Fe and Mg are highly soluble and will react with the phosphate ions (H2PO4 -) to form hydroxyl-phosphate which is insoluble and unavailable for plants. The low contents of available P observed in the soils of the study area were in agreement with the studies made by Mbene et al (2017) on soils collected within this region. There is a relationship between adsorption and soil physicochemical properties.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…At these pH values, Al, Fe and Mg are highly soluble and will react with the phosphate ions (H2PO4 -) to form hydroxyl-phosphate which is insoluble and unavailable for plants. The low contents of available P observed in the soils of the study area were in agreement with the studies made by Mbene et al (2017) on soils collected within this region. There is a relationship between adsorption and soil physicochemical properties.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Debicka et al (2016) carried out a similar investigation like Borggaard et al (1990) but used calcium chloride as the background electrolyte and concluded that OM was the main soil constituent, which increased P binding and limited P leaching from sandy soils. The interpretation of the results, therefore, could be that the organic matter in the soil solution might have blocked P adsorption sites (Hunt et al, 2007;Mbene et al, 2017), even though its removal slightly affected these binding sites (Table 4) but it increased the soil surface area which is responsible for the increase in P maximum adsorption (Table 5). Since was the dominant cation (Table 3) in these cultivated soils, phosphate behaviour in volcanic soils should be better simulated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Adsorption of P on Cameroonian acid soil had let to different conclusion as to the best fit isotherms. Previous work on the fixation of P on soil of the Eastern flank of Mount Cameroon displayed a best fit with a Freundlich model even though both isotherms had a coefficient of determination greater than 0.9 (Mbene et al, 2017). Comparing the P sorption maximum obtained from a Langmuir isotherm of the unamended soil (i.e.…”
Section: Resultsmentioning
confidence: 95%
“…Tropical soils in Africa are mostly acidic (Takow et al, 1991) and acidic soils are widely spread in the western region of Cameroon (Tematio et al, 2004) which presents critical levels of P (Tchuenteu, 1997). This is because of a high level of fixation via reaction with hydr(oxides) of Al and Fe found in clay minerals thus depriving P to plants resulting in poor growth (Mbene et al, 2017; Yadav et al, 2012). The fixation of P in soils is influenced by soil organic matter, pH, exchangeable Al, Fe, amount and type of silicate clays, calcium carbonate content (Eriksson et al, 2015; Gérard, 2016; Guppy et al, 2005) which affect soil biogeochemical processes (dissolution, adsorption and precipitation).…”
Section: Introductionmentioning
confidence: 99%
“…Unavailability of P for plants' uptake may be due to extreme soil pH. Under extreme acidity, P is adsorbed or held in active sites of the soil particles surfaces (Idris and Ahmed, 2012;Mbene et al, 2017). In acid soils, P reacts with oxides and hydroxides of Fe and Al, while in alkaline soils, P reacts with the oxides and hydroxides of cCa (Dabessa et al, 2018).…”
Section: Phosphorusmentioning
confidence: 99%